Shantiban forest patch as an oasis for birds in Pokhara city - Oli, Sundar; Dahal, Krishnaa; B.C., Grisma Kumar; Shrestha, Ananda Kumar; Shrestha, Ganga; Shrestha, Mohan Bikram (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Urban forests provide recreational sites for urban dwellers and are equally important for resident as well as migratory bird species. Shantiban is a small forest patch in the middle of the Pokhara city. This green space has been serving as an important habitat for birds. Seasonal surveys were carried out in 2023 and 2024 to comprehend bird composition and importance of urban forest patches by applying Non-Metric Dimensional Scaling (NMDS) with Bray–Curtis Dissimilarity. A total of 81 bird species were documented and Shannon Index of 3.53 (3-07-3.48) and Pielou’s Evenness of 0.80 (0.81-0.86) were obtained. Species richness and diversity index were significantly higher in the winter than in the summer, with a total of 15 species across both seasons. Season and year have significant effects on bird composition (PERMANOVA: F = 7.90, R2 = 0.40, p = 0.001), explaining 40% of the variation, while season alone explained 22% of the variation and year alone explained 8% of the variation in the bird community. Moreover, the NMDS plot also showed distinct clustering of the bird community by season and year. Despite its small size, Shantiban supports diverse avifauna, underscoring the ecological significance of conserving small urban green spaces for biodiversity and sustainable city environments.